Public Health Emergency Tabletop Exercise - John Mahoney (Association of American Medical Colleges, 2006)
Abstract This resource is an interactive tabletop exercise portraying the early response to a public health emergency. Participants confront the challenges of detecting and identifying a public health emergency and initiate the response to the outbreak. Since process and decision making are more important than minute details, emphasis is placed on developing the best possible response through problem identification, coordination, and integration of capabilities. Major goals are to expose learners to the complexities of responding to a public health emergency and to the concept that the medical aspects of response are not necessarily the primary components. Ethical principles and the importance of collaborative efforts are also emphasized. The case does not assume any prior knowledge of a specific disease. The exercise combines role-play with a group approach to an ill-defined problem, comparable in some regards to typical problem-based learning. After a large-group situation briefing, participants break out into working groups and discuss probable actions and coordination efforts. Questions provided serve as a guide for group discussion. The group may choose to discuss additional topics. Facilitators guide and mediate the group discussions. Most students felt the overall quality of the exercise was good or outstanding. Students highly valued the hands-on nature of the session and remarked on the importance of the topic. One measure of the effectiveness of this package is that both students and faculty repeatedly indicated that it was useful and timely and that it should continue to be part of the core curriculum. This exercise provides an opportunity to address operational and policy-level responses to a public health emergency.